Business models and cognition - Sund, Kristian J.; Galavan, Robert J.; Bogers, Marcel (New horizons in managerial and organizational cognition ;, 2020)
The concept of the business model has become very popular in the strategy and innovation literature's. Recent research has acknowledged its cognitive underpinnings, its status as a mental construct, and has highlighted how managers' cognitive and social sense-making patterns influence business model design and how shared logics enable innovation. Yet, the specific cognitive underpinnings of business models, though often mentioned, are rarely explicitly studied. Business Models and Cognition addresses this gap by focusing directly on intersections between business model studies and cognitive studies. Gathering an international, multidisciplinary team of business model and cognition scholars, this book not only identifies surprising connections between these two existing literature's, but also offers new reflections on future avenues of research for both in order to explore the cognitive foundations of business modelling. For its interdisciplinary scope, scholarly rigor, and novel insights, this fourth volume of the New Horizons in Managerial and Organizational Cognition is a must-read for scholars and students of business, strategy and cognition, and it is of keen interest to executives and managers eager to reflect critically on their own understanding of the "business model" as a concept.